Fluvial connectivity drives carbon cycle dynamics in a tropical mega‐delta - Adrian M. Bass; Wenguang Tang; Andrew C. G. Henderson; Virginia N. Panizzo; James Fielding; Abhra Chanda; Souvik Shil; Tuhin Ghosh; Charlotte Slaymark; Andy Large (Limnology and Oceanography, 2026)
Coastal estuaries are hotspots of biogeochemical cycling, biodiversity, and sediment processing, yet the drivers of carbon cycle processes remain poorly constrained. Here, we elucidate the influence of hydrological connectivity on carbon biogeochemistry in the Indian Sundarban over successive monsoon seasons by comparing hydrologically connected channels with perennial freshwater flow to channels isolated from feeding rivers. Results demonstrate dissolved organic carbon (DOC) and particulate organic carbon (POC) varied significantly with both season and connectivity. Dissolved organic carbon peaked pre‐monsoon and POC during the monsoon, with higher concentrations in hydrologically connected sites. Dissolved inorganic carbon (DIC) declined during the monsoon season but showed no connectivity effect. Elevated DOC relative to conservative mixing was attributed to freshwater runoff or groundwater input. Isotope data (δ 13 C) indicated POC respiration dominated during pre‐ and post‐monsoon, while DOC flocculation during the monsoon controlled POC dynamics, particularly in connected sites. Carbonate dissolution primarily regulated pre‐monsoon DIC, while organic matter degradation dominated in the monsoon and post‐monsoon periods. CO 2 efflux, measured across all sites, was consistently a source to the atmosphere and two to four times higher in connected channels, with higher turbulence driving maximum fluxes. Our findings demonstrate that hydrological connectivity fundamentally structures estuarine carbon cycling, lowering organic carbon concentrations and enhancing CO 2 fluxes. Shifts in global coastal delta sediment dynamics, in association with anthropogenic river management, therefore, have the potential to significantly alter delta carbon dynamics on a global scale.

Causes and consequences of tipping points in river delta social–ecological systems - Emilie Cremin; Cai J. T. Ladd; Thorsten Balke; Sumana Banerjee; Ly H. Bui; Tuhin Ghosh; Andy Large; Hue Thi Van Le; Kien V. Nguyen; Lan X. Nguyen; Tanh T. N. Nguyen; Vinh Nguyen; et al. (Ambio, 2024)
The sustainability of social–ecological systems within river deltas globally is in question as rapid development and environmental change trigger “negative” or “positive” tipping points depending on actors’ perspectives, e.g. regime shift from abundant sediment deposition to sediment shortage, agricultural sustainability to agricultural collapse or shift from rural to urban land use. Using a systematic review of the literature, we show how cascading effects across anthropogenic, ecological, and geophysical processes have triggered numerous tipping points in the governance, hydrological, and land-use management of the world’s river deltas. Crossing tipping points had both positive and negative effects that generally enhanced economic development to the detriment of the environment. Assessment of deltas that featured prominently in the review revealed how outcomes of tipping points can inform the long-term trajectory of deltas towards sustainability or collapse. Management of key drivers at the delta scale can trigger positive tipping points to place social–ecological systems on a pathway towards sustainable development.

“Local people want to keep their sand”: Variations in community perceptions and everyday resistance to sand mining across the Red River, Vietnam - Hannah Runeckles; Christopher R. Hackney; Hue Le; Hue Thi Thu Ha; Ly Bui; Do Thu Nga; Andy Large (The Extractive Industries and Society, 2023)

Aligning the Global Delta Risk Index with SDG and SFDRR global frameworks to assess risk to socio-ecological systems in river deltas - Emilie Cremin; Jack O’Connor; Sumana Banerjee; Ly Ha Bui; Abhra Chanda; Hieu Hong Hua; Da Van Huynh; Hue Le; Sonia Binte Murshed; Salehin Mashfiqus; Anh Vu; Zita Sebesvari; et al. (Sustainability Science, 2023)
River deltas globally are highly exposed and vulnerable to natural hazards and are often over-exploited landforms. The Global Delta Risk Index (GDRI) was developed to assess multi-hazard risk in river deltas and support decision-making in risk reduction interventions in delta regions. Disasters have significant impacts on the progress towards the Sustainable Development Goals (SDGs). However, despite the strong interlinkage between disaster risk reduction and sustainable development, global frameworks are still developed in isolation and actions to address them are delegated to different institutions. Greater alignment between frameworks would both simplify monitoring progress towards disaster risk reduction and sustainable development and increase capacity to address data gaps in relation to indicator-based assessments for both processes. This research aims at aligning the GDRI indicators with the SDGs and the Sendai Framework for Disaster and Risk Reduction (SFDRR). While the GDRI has a modular indicator library, the most relevant indicators for this research were selected through a delta-specific impact chain designed in consultation with experts, communities and stakeholders in three delta regions: the Red River and Mekong deltas in Vietnam and the Ganges–Brahmaputra–Meghna (GBM) delta in Bangladesh and India. We analyse how effectively the 143 indicators for the GDRI match (or not) the SDG and SFDRR global frameworks. We demonstrate the interconnections of the different drivers of risk to better inform risk management and in turn support delta-level interventions towards improved sustainability and resilience of these Asian mega-deltas.